Long-term outcomes of reduced-dose bleomycin in electrochemotherapy for basal cell carcinoma in elderly patients - Aleš Grošelj; Črt Jamšek; Simona Kranjc Brezar; Maja Čemažar; Maša Omerzel; Luka Pušnik; Gregor Serša (Scientific Reports)
Abstract Electrochemotherapy (ECT) is a minimally invasive treatment option for basal cell carcinoma (BCC), which is particularly advantageous in the elderly population. This study evaluated the long-term effects of treating BCC in older patients using ECT with a reduced dose of bleomycin (10,000 IU/m2) and compared the results to patients who received the standard dose of bleomycin (15,000 IU/m2). The retrospective analysis included 116 patients aged over 65 years with 257 histologically confirmed BCCs. Tumors were treated with either the standard dose (n = 82) or the reduced dose (n = 175) of bleomycin. The results showed that the recurrence rate was comparable between the groups, particularly in the first year after treatment. The reduced-dose group exhibited a greater recurrence rate after the first year, which may be attributed to a weaker local immune response due to the de-escalated dose of bleomycin. Nonetheless, administering a standard bleomycin dosage as a salvage treatment in the event of recurrence proved highly effective. These findings suggest that ECT with a reduced bleomycin dose is a viable option for treating BCC in elderly patients, particularly those with shorter life expectancy.